Pengaruh Financial Distress Dan Ukuran Perusahaan Terhadap Auditor Switching - Lembah Dewi Andini; Muhammad Azzaki; Reiza Basariadi; Sistya Rachmawati (JURNAL AKUNTANSI DAN AUDIT TRI BHAKTI, 2023)
This study aims to determine the effect offinancial distress and firm size on auditor switching. The independent variables in this study are financial distress and firm size. The dependent variable is auditor switching. The research method uses quantitative methods. The population in this study are mining companies listed on the Indonesia Stock Exchange (IDX) during 2017- 2021. The sample of this study were 44 companies listed on the Indonesia Stock Exchange (IDX). The analysis technique usedin this study is multiple linear regression. The results showed that profitability measured by Debt Equity Ratio (DER) did not significant on Auditor Switching and Firm Size measured by (Ln total assets) had a significantly effect on Auditor Switching.